Physics in Medical Science - Poudel, Parashu Ram (Himalayan Physics, 2011)
The domain of Physics covers vast area of scientific knowledge. Basic research on assemblies of atomic or nuclear radiation and gyromagnetic moments led to powerful technique for studying molecular structure as well as solid lattices. It led to invention and development of modern medical diagnostic and theraputic tools which have revolutionized the medical practices. Advancement in medical researches as seen today will be well-nigh impossible without the use of the finding of Physics. The funding made on Physics is in fact another way of funding made on human health. Keywords: Radioactivity; Crystallography; Radioimmune assay; MRI; CAT; PET The Himalayan Physics Vol.2, No.2, May, 2011 Page: 43-46 Uploaded Date: 1 August, 2011